أﺛﺮ طﺮﯾﻘﺔ اﻟﺘﻌﻠﯿﻢ اﻟﻤﺒﺮﻣﺞ ﻓﻲ اﻟﺘﺤﺼﯿﻞ اﻟﺪراﺳﻲ ﻟﻤﺎدة اﻟﻌﻠﻮم اﻟﻌﺎﻣﺔ )اﻟﻔﯿﺰﯾﺎء (ﻟﺪى طﺎﻟﺒﺎت اﻟﺼﻒ اﻟﺜﺎﻟﺚ ﻓﻲ ﻣﻌﺎھﺪ إﻋﺪاد اﻟﻤﻌﻠﻤﺎت (Journal of the College of Education for Women, 2019)
The goal of this research is to identify the effect of the programmed teaching method on the academic gaining for the material of general sciences (physics) for the female pupils in the third class in the teachers preparing institutes . And The research sample included 70 pupils after excluding the pupil who failed for the academic year ٢٠٠٨ -٢٠٠٩ , represented by two classrooms and one classroom was chosen random ally which contained 35 pupils, to represent the experimental group which studied by the programmed method, and the second group (35) pupils represent the controlling group, which studied by the lecturing method, then we made equivalence between the two groups in the previous knowledge in the third class intermediate school in physics (force, movement, work, ability and power), as well we made balance between the two groups in variables related to the experiment procedures which effect the inner safety for current research like the material of study, number of lessons and the studying hours, also we balanced the two groups in the variables related to the outside environment like lighting and the noise. And after setting the educational goals (the general, the private, the behavioral) for the studied subjects and in their three do mines (knowledge, the skill and psychological), according to teaching plan set for this purpose which was demonstrated on experts and specialists in physics, and the method of teaching to identify the availability, the experiment lasted for (15 weeks) and at the end the researcher had applied subjective test of choosing type consisted of (30 items after excluding 10 items from 40 original items i.e. 25% of the test items, then we got the item difficulty coefficient, and their distinguishing after the applying on the surveying sample, then we got the stability coefficient which was (0.88) by using halves divisions methods, as well used the apparent stability and the contents stability for the test items by showing it to experts in teaching and physics and the self stability for the test by using standing coefficient from the following equation: Self stability coefficient = standing coefficient ,andit was (0.93) And used the percentage and test to check the research goal and its assumption : And in the light of the results there is effectiveness of the programmed teaching method on the academic gaining on the lecturing method in the material of physics in the third class in the female teachers preparing institute, and there are differences of statistical references for the benefit of the experimental group, which got knowledge by the programmed teaching method where we nullify the zero assumption which stated: (there are no individual differences of statistical references between the averages of the pupils who studied by the programmed teaching method and the marks of the pupils who studied by the lecturing method on the academic gaining for the material of general sciences (physics) for the third class female teachers preparing institute.